2010
DOI: 10.1073/pnas.1004664107
|View full text |Cite
|
Sign up to set email alerts
|

H2-O, a MHC class II-like protein, sets a threshold for B-cell entry into germinal centers

Abstract: Upon antigen (Ag) encounter, B cells require T-cell help to enter the germinal center (GC). They obtain this help by presenting Agderived peptides on MHC class II (MHCII) for recognition by the T-cell receptor (TCR) of CD4 + T cells. Peptides are loaded onto MHCII in endosomal compartments in a process catalyzed by the MHCII-like protein H2-M (HLA-DM in humans). This process is modulated by another MHCII-like protein, H2-O (HLA-DO in humans). H2-O is a biochemical inhibitor of peptide loading onto MHCII; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…Thus, the maintenance of H2-O expression in B cells after challenge with TLR agonists would help to prevent B cells from presenting high levels of MHCII-peptide early in immune responses, thus promoting DC MHCII presentation and naïve CD4 T cell activation only by DCs. Support for this idea is provided by our recent studies showing that the presence of H2-O in naïve B cells reduces the ability of B cells to gain T cell help (14). Collectively, the studies presented here show the specific downregulation of H2-O in CD8α − DCs following activation and further highlight the importance of the developmental control of optimal MHCII presentation by DCs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the maintenance of H2-O expression in B cells after challenge with TLR agonists would help to prevent B cells from presenting high levels of MHCII-peptide early in immune responses, thus promoting DC MHCII presentation and naïve CD4 T cell activation only by DCs. Support for this idea is provided by our recent studies showing that the presence of H2-O in naïve B cells reduces the ability of B cells to gain T cell help (14). Collectively, the studies presented here show the specific downregulation of H2-O in CD8α − DCs following activation and further highlight the importance of the developmental control of optimal MHCII presentation by DCs.…”
Section: Discussionmentioning
confidence: 91%
“…Recent evidence has indicated that H2-O/DO modulation of MHCII peptide presentation can have important biological consequences. H2-O expression has been shown to reduce the ability of B cells to gain T cell help and participate in the germinal center reaction potentially setting a threshold for B cell entry into germinal centers (14). Additionally, modulation of antigen presentation by DO expression in NOD DCs results in the prevention of the autoimmune disease, type 1 diabetes (15).…”
Section: Introductionmentioning
confidence: 99%
“…In immature DCs, DO is thought to increase the range of presented peptides, therewith facilitating tolerance induction to a broad range of self peptides (Yi et al 2010). DO expression is down-regulated in activated B cells and DCs, enhancing DMcatalyzed peptide loading under inflammatory conditions (Glazier et al 2002;Hornell et al 2006;Draghi and Denzin 2010;Porter et al 2011).…”
Section: Endosomal Mhc Class II Processingmentioning
confidence: 99%
“…Constitutive overexpression of DO in dendritic cells blocks disease in the nonobese diabetic (NOD) mouse model of type 1 diabetes (18). Finally, DO expression in murine B cells limits their participation in the germinal center reaction through effects on antigen presentation (19). However, the full physiological function of DO is still unclear.…”
mentioning
confidence: 99%